A mechanistic study of molecular CO2 interaction and adsorption on carbon implanted SnS2 thin film for photocatalytic CO2 reduction activity. (June 2020) - Billo, Tadesse; Shown, Indrajit; Anbalagan, Aswin kumar; Effendi, Tirta Amerta; Sabbah, Amr; Fu, Fang-Yu; Chu, Che-Men; Woon, Wei-Yen; Chen, Ruei-San; Lee, Chih-Hao; Chen, Kuei-Hsien; Chen, Li-Chyong
Abstract: Gas-phase photocatalytic reactions to convert carbon dioxide and water into oxygen and hydrocarbons are the foundation of life on earth. However, the efficiency of photosynthesis is relatively low ( 1%), which leaves much room for artificial photosynthesis to reach the benchmark of the solar cells (>15%). In this work, carbon implanted SnS2 thin films (C–SnS2 ) were prepared to study photocatalytic activity and adsorbate-catalyst surface interactions during CO2 photoreduction. The electron density distribution in C–SnS2 and its contribution toward the photogenerated charge transfer process has been analyzed by the angle-dependent X-ray absorption near-edge structure (XANES) study. The C–SnS2 surface affinity toward the CO2 molecule was monitored by in-situ dark current and Raman spectroscopy measurements. By optimizing the dose during ion implantation, SnS2 thin film with 1 wt% carbon incorporation shows 108 times enhancement in the CO2 conversion efficiency and more than 89% product selectivity toward CH4 formation compared with the as-grown SnS2 without carbon incorporation. The improved photocatalytic activity can be ascribed to enhanced light harvesting, pronounced charge-transfer between SnS2 and carbon with improved carrier separation and the availability of highly active carbon sites that serve as favorable CO2 adsorption sites. Graphical abstract: Image 1 Highlights: Carbon implanted SnS2 thin-film and its contribution toward the photogenerated charge transfer process for CO2 reduction. The C-SnS2 shows 108 times enhancement in the CO2 conversion efficiency and higher product selectivity compared with SnS2 . The CO2 interactions with the catalyst surface and their implications on heterogeneous photocatalytic CO2 reduction.